Analysis of day-to-day variations in air temperature in the region of Siedlce - Elżbieta Radzka; Marlena Radzka; Maria Markowska (Acta Scientiarum Polonorum. Formatio Circumiectus, 2024)
Aim of the study: As a result of the increase in average air temperature associated with the present-day climate change, heatwaves are forecast to occur with increasing frequency. What is more, they will be longer, more intense, and potentially very dangerous for human health and life. The present work reports the day-to-day variation in air temperature and the variation of thermally characteristic days in Siedlce from 2001 to 2023.